Pengaruh Good Corporate Governance terhadap pengungkapan enterprise risk management pada perusahaan manufaktur - Oktaviana, Indika Riski; Puspitasari, Elen (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Every company that carries out business activities will definitely face a risk. The risks that arise are unavoidable, so the company must prepare ways to handle the risks that will occur. This study examines the effect of the implementation of Good Corporate Governance in terms of independent commissioners, the size of the board of commissioners and the auditor's reputation on the disclosure of Enterprise Risk Management in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period of observation. This study uses quantitative research. with descriptive method. There are 73 sample companies obtained from purposive sampling technique by producing 219 observational data. The analytical technique used is multiple regression analysis using SPSS 22 software. The results obtained indicate that independent commissioners, board size and auditor reputation affect the use of Enterprise Risk Management.